Students’ Perceptions of Enjoyable Listening Activities in a Low Exposure EFLClassroom at MTS. Zainul Irsyad - Nuriyatul Maftuhah; Feri Ferdiyanto; Nina Agus Hariati (Universitas Pahlawan Tuanku Tambusai, 2026)
Listening is a significant skill in English as a Foreign Language (EFL) instruction, especially in low-exposure settings where students have limited contact with English outside the classroom. However, many students struggle and demonstrate low motivation as a result of monotonous teaching approaches and a lack of engaging activities. Previous research has mostly focused on learning outcomes rather than students' perceptions of enjoyable listening activities. Furthermore, little research has explored students' perceptions in low-exposure settings. As a result, the purpose of this study is to investigate students' perceptions and determine the types of listening activities they enjoy the most. This study used a qualitative case study approach with students from MTs. Zainul Irsyad. Data were obtained through classroom observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that while students initially have negative perceptions, they respond positively to participatory activities such as songs, videos, and group discussions. Finally, enjoyable and interactive activities increase students' interest and motivation in learning through listening.